FAKTOR-FAKTOR YANG MEMPENGARUHI CASH HOLDING PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI - Stefany Liputri, Liana Susanto (Jurnal Paradigma Akuntansi, 2020)
An increase in the company's cash holdings will create better corporate policies of storage company cash to accumulate cash reserves and making reinvestments. This research uses 33 manufacturing companies listed on the Indonesia Stock Exchange that have been selected using a purposive sampling method from a total of 137 companies in a three-year period. This research used panel data analysis to test the relationships between cash holdings and the identified determinant factors such as profitability, leverage, net working capital and capital expenditure. The data in this research were processed using the Eviews version 10 program. This research concludes that profitability, leverage, net working capital and capital expenditure significantly effect on cash holding of manufacturing companies in Indonesia.